Um mundo em vários movimentos : uma etnografia sobre futebolistas de base - Palmiéri, Júlio César Jatobá (2015)
The theme of this thesis is the youth football. Its practitioners, the youth footballers, are possessed of varying talents, factors that distinguish them in a marketing scale that streamlines the exchange in the football universe. Looking for professional football, they start from the football gift recognized and nurtured by those 8 who surround them, adding many other values, in a practical and symbolic order, which depend on the relationships established within the institutional framework of this sport and that has to do with other players, coaches, directors, supporters, family members, agents and specialized media, but also with all the environment where they live those experiences. We can glimpse, thus, the dynamics of a "sports ecology" approached from a multi-sited perspective where I present part of some meshwork relations that produces surfaces in formation and constant movement and instability, whose relations among the actors are mobilized around what is defined by producing sports talents, commonly stabilized by some categorizations taken here by issues such as projects, professional career and sportive trajectory. The scenario considered is the youth football in Brazil and part of South America (Uruguay and Argentina), between clubs and national teams (under 15 and under 17), seeking to understand how the world of youth footballers is created and reproduced in and out of the pitch.